Kewenangan Pengadilan Tata Usaha Negara Serang dalam Menyelesaikan Sangketa Sertifikat Ganda Atas Tanah di Kabupaten Lebak (Studi Kasus Putusan Nomor : 5/G/2020/PTUN.SRG) - Siti Anis Khoirunnisa; Nurikah Nurikah; H E Rahmat Jazuli (Sultan Jurisprudence: Jurnal Riset Ilmu Hukum, 2021)
The authority of the State Administrative Court according to Law Number 5 of 1986 concerning the State Administrative Court is to examine, decide and resolve disputes. One of the case studies is Decision No. 5/G/2020/PTUN.SRG the object of the dispute is a Certificate of Ownership that has been issued by the Head of the Lebak Regency BPN on land belonging to other people which results in mutual accusations. So the problem in this research is how is the authority of the Serang Administrative Court in resolving dual land certificates? and what is the basis for the judge's legal considerations on Decision Number 5/G/2020/PTUN.SRG? The research method that the author uses in the preparation of this legal writing is using the normative juridical method, namely research called library research because it focuses on secondary data research, with descriptive analytical research that discusses the resolution of dual certificate disputes over land in Lebak Regency which is sourced from primary data. and secondary data. Data collection techniques consist of literature study. And the method used in analyzing the data is a qualitative juridical analysis. The results of the study concluded that the Serang Administrative Court in completing the dual certificates. Decision No. 5/G/2020/PTUN.SRG is based on relevant evidence, namely seeing violations committed by the Head of the Lebak Regency BPN Office in the measurement and mapping process as well as procedures for issuing replacement certificates regulated in Article 17 paragraph 2 and Article 18 paragraph 1 and paragraph 4 PP No. 24 of 1997 concerning Land Registration. So the Panel of Judges canceled the Certificate of Ownership in Nji's name. Chusdajah Binti Sarbini.